Pengembangan Panduan Layanan Informasi Pencegahan Pelecehan Seksual: Sebuah Pendekatan Contextual Teaching and Learning - Sulistyawati, Nurwinda; Alfath, Annajmi (Institut Agama Islam Negeri Curup, 2024)
Sexual harassment is increasingly rampant in people's lives, this can become a big problem both personally and socially for students, if there is a lack of understanding and knowledge about positive attitudes towards sexuality. One of the efforts to provide understanding, knowledge and prevention that can be carried out by BK Teachers is through providing information services. In order to be more focused on the sources of information obtained, a learning media product was created in the form of a guide to providing information services as a form of preventing sexual harassment. This research was conducted with the aim of developing a sexual harassment prevention information service guide (using a Contextual Teaching and Learning approach). Using the ADDIE model development research method (Analyze, Design, Development, Implementation and Evaluation), with small group research subjects consisting of 3 experts and 3 guidance and counseling teachers. The results of the research show that the sexual harassment prevention information service guide (using the Contextual Teaching and Learning approach) is valid and can be used by guidance and counseling teachers to improve the prevention of sexual harassment.